Katie's way - Perry, Marta (New York : Berkley Books, 2011)
After a thwarted romance, Katie Miller starts over by moving to Pleasant Valley and opening a quilt shop. When acts of vandalism threaten Katie's shop, she turns to furniture maker, Caleb Brand, and their friendship deepens. But will Caleb's secret past prevent him from embracing a future with Katie? Or will their fragile romance develop the strength to last a lifetime.
Includes an excerpt from Hannah's Joy ; Pleasant Valley, Book 6, by Marta Perry (p. 339-343).
Keywords: Amish -- Fiction; Quilting -- Fiction; Quiltmakers -- Fiction; Lancaster County (Pa.) -- Fiction; Christian fiction; Love stories